Pengendalian Internal Pada Supply Chain Management Perusahaan Konstruksi - Wahyuni, Rahmi Sri; Yusuf Khudri, Tubagus Muhamad (E-Jurnal Akuntansi, 2024)
This study aims to evaluate the implementation of internal control in the supply chain management of PT X (Construction Company) by referring to Internal Control COSO 2013. This case study research uses a qualitative approach with data collection methods carried out are observation, document analysis and interviews. Data were analyzed using content analysis. The results showed that the implementation of internal control was inadequate in terms of the control environment, risk assessment, control activities, information and communication and monitoring activities. Each component has weaknesses in its application. Thus, it can be concluded that the application of internal control is inadequate in the supply chain management of PT X